A Co-integration Analysis of the Dominican Republic’s Aggregate Import Demand Function under a Floating Exchange Rate Regime - Grullón, Santiago (Asian Economic and Financial Review, 2012)
This paper presents an empirical examination of the responsiveness of aggregate imports to variations in relative prices and domestic economic activity in the Dominican Republic under a floating exchange rate regime implemented in 1985. Using the „bounds‟ testing approach to co-integration of Pesaran et al. (2001) and a method developed by Bårdsen (1989) to derive long-run price and income elasticities of import demand for the period of 1985-2005, the findings show the existence of a co-integration relationship between imports, relative prices and domestic income. Total imports have a long-run price demand elasticity of -1.61, indicating that relative prices have a strong effect on their demand and thus signifying that the demand for imports is strongly affected by domestic inflationary pressures. Moreover, the long-run domestic income demand elasticity is +1.24, demonstrating that imports are strongly affected by domestic economic activity. This latter result is shown to have important implications for sustainable economic growth in the Dominican Republic, particularly in the light of its recent membership in the Central American Free Trade Agreement (DR-CAFTA).